Transformasi Pendidikan dalam Islam: Menjelajahi Filsafat Pendidikan Islam di Era Modern - Haidar M Alfatih; Nurul Aini (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2023)
The transformation of Islamic education is an inevitable historical process inseparable from social, cultural, and scientific developments in the modern era. Islamic education, philosophically rooted in the Qur’an and Sunnah, faces challenges from globalization, modernity, secularization, and technological advancement, requiring paradigm renewal without losing its core values. This article aims to analyze the transformation of Islamic education from the perspective of Islamic educational philosophy by examining classical and contemporary scholarly discourse and its relevance to modern educational contexts. This study employs a qualitative library research method, analyzing reputable national and international journal articles. The findings reveal that the transformation of Islamic education occurs through integrating tawhid-based values, moral education, and Islamic epistemology with modern pedagogical approaches such as critical learning, educational technology, and integrative curricula. Furthermore, the study highlights the contributions of modern Muslim thinkers in reconstructing educational goals, methods, and orientations to ensure relevance and contextuality. This research concludes that Islamic educational philosophy serves as a normative and conceptual foundation for developing an adaptive, holistic Islamic education system oriented toward forming insan kamil in the modern era.